D’imagier à ymaginero : la présence de sculpteurs septentrionaux en Espagne aux xve-xvie siècles - María Teresa Rodríguez Bote (Bulletin du Centre d’Études Médiévales d’Auxerre)
Renaissance sculpture in Spain welcomes an important migration flow of carvers from northern countries, mainly from France ; most of them settle down in the former Kingdom of Castile. Despite this trend starting in the Middle Ages, it is along the 16th century when this stream is more numerous. Not only have they played an important role in the introduction of Italian-style ornamental items, but also opened their own workshops, where new apprentices were taught. Many of these foreign carvers enjoyed a solid professional reputation and developed a highly successful career.